Socio-Psychological Criteria of the Formation of Gender Stereotypes of Appearance - Shyian, Oksana M.; Foster, Larysa F.; Kuzmenko, Tatiana M.; Yeremenko, Larysa V.; Liesnichenko, Nina P. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The article considers the socio-psychological criteria for the formation of gender stereotypes of appearance. The priority of the study is implementing a system of criteria for gender stereotypes of appearance, taking into account the system of socio-psychological factors and gender-oriented forms of prevention of overcoming sexism and discrimination on the grounds of personality attractiveness. It is substantiated that social evaluation through physical criteria creates several psychological problems because the "physical self" is an essential component of the "self-concept" and one of the criteria of self-esteem. It is proved that the properties of gender stereotypes coincide with the social ones. They are the bearer of emotional and evaluative characteristics, taking into account the group of values associated with the ambivalence of ideas about another. A methodical approach to the assessment of gender stereotypes of appearance and personality is proposed, which allows determining the criteria of human well-being, taking into account discrimination factors, intrapersonal parameters of affective-negative perception of one's appearance and self-concept, as well as the aesthetic perception of identity. An assessment of socio-psychological factors of gender stereotypes of appearance, which is based on the methodological provisions of psychoanalysis and humanism, cognitive paradigm, dispositional theory, cross-cultural approach, and some sociological studies, is carried out. As an experiment on empirical verification of the stereotypes of appearance, their gender differences, and socio-psychological factors, a set of methods of psychological diagnosis is used, which allow determining indicators of stereotypes of appearance, self-esteem, and attitude to beauty; socio-psychological criteria for the formation of gender stereotypes of appearance. A methodology for assessing the criteria for improving the attitude of respondents to their own appearance by determining the level of self-esteem, satisfaction with appearance, awareness of gender differences in appearance, and the desire to improve their own appearance in case of discrimination has been developed and implemented.